Characterization of Water-Soluble Ions in PM2.5 in Chongqing, a Megacity in Eastern Sichuan Basin, China - Song, Tianli; Cao, Xuyao; Wang, Huanbo; Qiu, Yang; Chen, Yang; Tian, Mi; Yu, Jianyan; Zhai, Chongzhi; Yang, Fumo (Journal of Environmental Science and Engineering Technology, 2020)
Samples of PM2.5 were collected at three urban sites and one rural site simultaneously in Chongqing, the only megacity in eastern Sichuan Basin, Southwest China, from October 15 to November 13, 2015. Water-soluble ions (WSIs, i.e., F–, Cl–, NO3–, SO42–, K+, Na+, NH4+, Mg2+ and Ca2+) in PM2.5 were measured to investigate their characteristics and formation pathways. The average concentrations of PM2.5 at the urban sites were 55.5–59.0 µg m–3, which was 62.8–73.0% higher than that at rural site. SO42–, NO3–, NH4+ were the dominant ions, contributing to more than 90% of total WSIs. The coefficients of divergence for SO42– between the urban and rural sites were 0.15–0.17, indicating its relatively uniform distribution across Chongqing. Analysis of the formation mechanisms of SO42– and NO3– in PM2.5 suggested that the heterogeneous reaction was responsible for the high concentrations of sulfate among the four sites, whereas nitrate was formed mainly through homogeneous reactions at the urban sites. Furthermore, the results of trajectory clustering showed that the air pollution were mainly from local sources within the basin. Our findings on PM2.5 composition in Chongqing help to advance the knowledge on PM2.5 pollution in Chinese megacities, and to provide more evidence for further pollution mitigation.